Solid particle erosion behavior of melt-infiltrated SiC/SiC ceramic matrix composites (CMCs) in a simulated turbine engine environment. (1st July 2021) - Panakarajupally, Ragav P.; Mirza, Farhan; El Rassi, Joseph; Morscher, Gregory N.; Abdi, Frank; Choi, Sung
Abstract: The erosion behavior of a melt infiltrated SiC/SiC ceramic matrix composite was investigated under a more representative engine environment. A special experimental facility was setup to simulate the turbine engine conditions. The influence of the operating parameters such as particle velocity, particle size, temperature, erodent concentration and impingement angle were investigated. In addition, room temperature studies were also conducted under the same operating parameters for comparison. Eroded sites were investigated under the scanning electron microscope (SEM) to understand the erosion mechanisms. The results indicate that erosion rate increased with increase in particle velocity, size and temperature. Also, at shallow impact angles the CMC shown to exhibit ductile like mode of erosion as opposed to brittle fracture mode at normal impact angles was observed. The erosion rate decreased with increase in erodent concentration which may be related to a particle shielding effect.